Pelaksanaan Rehabilitasi Bagi Warga Binaan Narkotika - Somoharjo, Hendrika Hutami; Hehanussa, Deassy Jacomina Anthoneta; Latupeirissa, Julianus Edwin (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2025)
Rehabilitation is a way or process of recovering narcotics abuse for addicts, abusers and victims who are carried out medically or socially in order to restore community members so that they no longer fall into narcotics. Rehabilitation is an alternative method determined by certain procedures and conditions. This study aims to analyze and explain the implementation of rehabilitation of prisoners of narcotics crimes in accordance with Law Number 35 of 2009 concerning Narcotics and Law Number 22 of 2022. Based on the analysis of the implementation of rehabilitation for prisoners of narcotics crimes, social rehabilitation activities are carried out by applying the Therapeutic Community method, which is a stage of rehabilitation where a person must strive to restore himself without being given facilities in general by carrying out the stages of recove. The results showed that based on the analysis of the implementation of rehabilitation for prisoners of narcotics crimes in accordance with Law Number 35 of 2009, although only social rehabilitation activities can be carried out by applying the Therapeutic Community method. This stage of rehabilitation is a stage of rehabilitation where a person must strive to restore themselves without being given facilities in general by carrying out stages of recovery. Meanwhile, the implementation of rehabilitation of prisoners in narcotics cases that can be carried out is only social rehabilitation while medical rehabilitation is the responsibility of BNN in collaboration with the Hospital.